Pelatihan Inovasi Produksi Kerupuk Guna Meningkatkan Ketahanan Ekonomi Desa Wonokromo Lamongan - Siti Musarofah; yanuangga galaherlambag; Maulidza Nurfauzi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
Lack of knowledge and skills in processing agricultural products, namely rice, which is able to become a product of economic value. So this Community Service aims to improve the knowledge and skills of the group of mothers in Wonokromo village through the transformation of processing technology, packaging, and marketing management with rice as basic ingredients into savory and delicious processed onion crackers. The target of this program is the formation of a business unit that is developing food products from the basic ingredients of rice/rice. Specifically, this program aims to train Housewives (IRT) in Wonokromo Village to produce onion crackers. This training is given starting from the way of processing, packaging, and marketing. This activity involved members of the Real Work Lecture students who were participated in by housewives (IRT) in Wonokromo village. The results achieved in this activity are the Housewives Group (IRT) in Wonokromo village has understood and has skills in entrepreneurship, and knows how to manage a more structured business, there are onion crackers products with a savory and delicious taste and understand how to market products. with the innovation of packaging and the use of technology. The results of the evaluation that have been carried out can be seen that the knowledge of participants regarding rice-based processing has increased and opened the minds of participants to take advantage of existing opportunities to increase income.